THE EFFECTS OF GRADIENT VELOCITY AND DETENTION TIME TO COAGULATION – FLOCCULATION OF DYES AND ORGANIC COMPOUND IN DEEP WELL WATER - Muhamad Lindu (Indonesian Journal of Chemistry, 2008)
The treatment of deep well water of Trisakti University by coagulation and flocculation using baffle channel system has been conducted. The detention time of hydrolic were varied. The coagulant dose was varied as 50, 100, 150, 200, 300, 350, 400, 450 and 500 ppm. Water of well sampel was added by coagulant with rotation velocity 200 rpm for 1 minute. The optimal coagulant dose was determined by measuring turbidity, colour, total suspended solids and organic compound. The result showed that the organic compound and colour of deep well water of Trisakti University could be reduced by coagulation and flocculation process by hydrolyc system. The optimal dose of the coagulant was 250 ppm. The removal efficiency of colour and organic compound using optimal dose for continuous flow reactor reached after water flow passed the reactor for 3 - 5 times detention time in the reactor. The optimal gradient velocity (G) was 30 - 35 sec-1 and collision energy (GT) was 65.000 - 79.000 to get optimal flocculation. With this condition, the removal efficiency of turbidity, colour and organic was more than 90%.